2016
DOI: 10.1186/s12885-016-2119-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor slice culture system to assess drug response of primary breast cancer

Abstract: BackgroundThe high incidence of breast cancer has sparked the development of novel targeted and personalized therapies. Personalization of cancer treatment requires reliable prediction of chemotherapy responses in individual patients. Effective selection can prevent unnecessary treatment that would mainly result in the unwanted side effects of the therapy. This selection can be facilitated by characterization of individual tumors using robust and specific functional assays, which requires development of powerf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
149
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(152 citation statements)
references
References 24 publications
2
149
0
1
Order By: Relevance
“…NSCLC slices cultured on rotating incubation units, to ensure continuous oxygenation, were fragile and showed dynamic culture‐induced changes, most prominently altered proliferation and mTORC1 hyperactivation. Although previous reports showed sustained viability of clinical tumour slices for 4–14 days , these studies derived conclusions from the selective analysis of cultured slices, whereas we systematically compared neighbouring cultured and uncultured slices. Furthermore, our study is the first to deeply analyse intratumour oncogenic signalling, and shows that signalling and proliferation alterations take place prior to overt changes in viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSCLC slices cultured on rotating incubation units, to ensure continuous oxygenation, were fragile and showed dynamic culture‐induced changes, most prominently altered proliferation and mTORC1 hyperactivation. Although previous reports showed sustained viability of clinical tumour slices for 4–14 days , these studies derived conclusions from the selective analysis of cultured slices, whereas we systematically compared neighbouring cultured and uncultured slices. Furthermore, our study is the first to deeply analyse intratumour oncogenic signalling, and shows that signalling and proliferation alterations take place prior to overt changes in viability.…”
Section: Discussionmentioning
confidence: 99%
“…Within the IMI‐PREDECT project (http://www.predect.eu), we developed a workflow for short‐term culture of tumour slices, and showed that organotypic supports and atmospheric oxygen are strict requirements for tissue viability . A number of other studies have shown that responses to cytotoxic agents or selected targeted compounds can be modelled in clinical tumour‐derived slices . However, the question remains of how the in situ spatial signalling heterogeneity affects the pharmacodynamics of signalling inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Primary tumour tissues from biopsy or surgical resection can be embedded in ECM and cultured as an in vitro model [30][31][32][33][34] (figure 2a). The embedded tumour sections retain the tumour vasculature, nearby stroma and the heterogeneity of the tumour cells.…”
Section: Ex Vivo Tumour Culturementioning
confidence: 99%
“…soft, mucinous or fatty tissue), where firm tissue consistency is required [213, 214]. Another drawback of slice cultures is the loss of viability within 5 to 7 days [211].…”
Section: The Use Of In Vitro and In Vivo Models For Guiding Precisionmentioning
confidence: 99%